1995
DOI: 10.1111/j.1365-2230.1995.tb01366.x
|View full text |Cite
|
Sign up to set email alerts
|

Acral persistent papular mucinosis in two sisters

Abstract: We describe two young sisters with an asymptomatic papular eruption on the forearms, the clinical, histopathological and ultrastructural features of which were consistent with acral persistent papular mucinosis. Familial occurrence of this uncommon disease is exceptional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…A recent review of all APPM cases described to date showed that, based on the above classification, the clinical and histological criteria of only 20 cases allow them to be convincingly labelled as APPM, underlining the rarity of this condition 5 . Interestingly, however, this condition was been noted in two sisters 6 . The lesions of APPM are usually asymptomatic, and no treatment is known to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of all APPM cases described to date showed that, based on the above classification, the clinical and histological criteria of only 20 cases allow them to be convincingly labelled as APPM, underlining the rarity of this condition 5 . Interestingly, however, this condition was been noted in two sisters 6 . The lesions of APPM are usually asymptomatic, and no treatment is known to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several cases of this entity have been reported. 17 , 19–21 Acral persistent papular mucinosis is characterized according to Rongioletti and Rebora 18 by 2–5 mm papules, symmetrically arranged on the dorsal aspects of the hands and wrists with occasional extension to the forearms, knees, and elbows. This entity has a chronic course, without paraproteinemia or other systemic associations.…”
Section: Discussionmentioning
confidence: 99%
“…It is rare in younger patients with only three patients who were less than 20 years of age at the onset of their lesions. [17,19] In our case the age of onset was lesion was 54 year. Lesions are generally asymptomatic, only three had pruriticlesions.…”
Section: Discussionmentioning
confidence: 99%
“…[2,[14][15][16] They mainly involve the back of the hands and wrists, the distal aspects of the forearms, and rarely the antecubital fossae. All cases described till date are sporadic except for a pair of sisters [17] and another patient's father having suspicious lesions. [18] According to review done by Di-Quing Luo et al APPM is more common in females, though we are reporting it in male adult.…”
Section: Discussionmentioning
confidence: 99%